Financial development and economic growth in selected Caribbean countries - Modeste, Nelson (Caribbean Centre for Monetary Studies [St. Augustine]TT, 1996)
Assesses the nature of the causal relationship between the financial development and economic growth in Barbados, Jamaica and Trinidad and Tobago.